Eliminating slavery and combating human trafficking : the relevant constitutional provisions and domestic and international laws - Mokhtar, Khairil Azmin (IIUM Press, 2011)
Slavery and forced labor have been accepted to be against humanity globally. These practices are expressly prohibited by the Federal Constitution in Malaysia. Although, the prohibition ofhuman trafficking is not expressly mentioned in the Constitution, it could be regarded as one ofthe most heinous crime according to the letter, intent and spirit ofthe constitution. This is related to the fuct that human trafficking is much associated with modem day slavery and therefore is against the ideology of the Malaysian nation and acceptable norms of international community